THE STATE POLICY ON PREVENTING WATER PROBLEMS DURING THE YEARS OF INDEPENDENCE (Scientific journal of the Fergana State University, 2023)
The State Policy of  Preventicy  Water  Problems during the Years of  Independence.In this article is given water problem, one of the main problems of the Republic of Uzbekistan and in connection with it all the defects done in this sphere during the existence of Soviet State are opened in it.In this article are also given the principal actions of the government of the Republic of Uzbekistan to overcome water problems. At the same are shown the legislative statements and their fulfillment  to solve the problems of water resources.